Estimation of the Relationship Between Learning Styles Inventory and Online Learning During the Pandemic - Rano Agustino; Santhi Pertiwi (ADI Publisher, 2020)
The learning model during the Covid-19 pandemic underwent a change in the teaching process. Where the changes are seen in the learning process, where face-to-face in the classroom turns into virtual online learning. This study will measure the extent of the relationship between student grades and their learning styles during the pandemic. The data that will be used are data from the questionnaire results of the Computer Faculty students from the University in Jakarta. This questionnaire was conducted on August 30, 2020. After the questionnaire dataset was fulfilled, it was integrated with student scores for those who took the questionnaire. To determine the learning style using David Kolb's Learning Style Inventory. While the statistical test uses Anova One Way and Post hoc. The results of data analysis will produce the learning style of each student. The results of data analysis will also recommend four roles for the teaching style of the teacher using the Kolb Educator Role Profile (KERP).